Pathogenesis, diagnosis and therapy of facial synkinesis: A systematic review and clinical practice recommendations by the international head and neck scientific group - Guntinas-Lichius, Orlando; Prengel, Jonas; Cohen, Oded; Mäkitie, Antti A.; Vander Poorten, Vincent; Ronen, Ohad; Shaha, Ashok; Ferlito, Alfio (Frontiers in Neurology, 2022)
Introduction: Postparalytic facial synkinesis after facial nerve injury produces functional disabilities and mimetic deficits, but also cosmetic and non-motor psychosocial impairments for the patients. These patients typically have a high continuous and high motivation for rehabilitation. The aim is to inform the affected patients and their therapeutic professionals (otorhinolaryngologist - head and neck surgeons; oral-maxillofacial surgeons, plastic and reconstructive surgeons, neurosurgeons, neurologists and mime therapists be it speech and language therapy- or physiotherapy-based) and to provide practical recommendations for diagnostics and a stepwise systematic treatment approach of facial synkinesis. Methods: In a first phase, a systematic literature search on the topic in PubMed and ScienceDirect starting from 2008 resulted in 132 articles. These were the basis for the review and a comprehensive series of consensus statements on the most important diagnostic tests and treatment options. In a second phase, one consensus paper circulated among the membership of the International Head and Neck Scientific Group until a final agreement was reached for all recommendations. Results: Diagnostics should include a standardized assessment of the degree of synkinesis using validated clinician-graded instruments and synkinesis-specific patient reported outcome measures. Treatments for facial synkinesis include facial training mainly based on facial biofeedback retraining, chemodenervation with botulinum toxin, selective neurectomy, myectomy, and any combination treatment of these options. Conclusion: A basic understanding of the pathomechanisms of synkinesis is essential to understand the treatment strategies. A standardized assessment of the synkinetic symptoms and of the individual synkinesis pattern is needed. First line treatment is facial training, and then botulinum toxin. Surgery is reserved for individual cases with unsatisfactory first line treatment.